Cost of quality assessment as IT system input for product quality analysis - Gruszka, Józef (Rachunek kosztów jakości jako źródło systemu informatycznego do analiz jakości wyrobu, 2019)
Changes on the global automotive market have driven automobile manufacturers and their suppliers to search for effective methods and tools to support management processes. Examples include cost-of-quality assessment and managerial accounting. The article outlines the cost components of quality losses based on data from an IT system and the author’s prior research into assessments of the cost of quality incurred by an automotive-industry supplier. It provides an assessment of the cost of quality to sales ratio as well as the cost of prevention, control and valuation. Once obtained, the cost of losses is used as a starting point for the identification of the costs of internal and external losses that contribute to total losses. Through research and analysis, the author identifies the underlying causes of the biggest losses in aluminum foundries resulting from product non-conformities and proposes ways to mitigate such losses by improving product quality
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 3 (53), s. 23-29
Keywords: cost-of-quality assessment; cost of loss; quality management system; rachunek kosztów jakości; koszty strat; system zarządzania jakością